PROTECTIVE EFFECTS OF DILTIAZEM ON THE MECHANICAL PERFORMANCE OF THE HYPOXIC MYOCARDIUM - Cicogna, Antonio Carlos [UNESP]; Padovani, Carlos Roberto [UNESP]; Brooks, W. W.; Schine, L.; Robinson, K. G.; Conrad, C. H.; Gaasch, W. H.; Bing, OHL (Associação Brasileira de Divulgação Científica (ABRADIC), 1993)
1. To determine whether diltiazem protects the hypoxic myocardium by reducing contractile work, we have compared the effects of diltiazem and quiescence on left ventricular (LV) papillary muscle subjected to hypoxia. Papillary muscles were obtained from male Charles River CD rats weighing 150-250 g.2. Four groups of muscles were studied: control (N = 6), non-stimulation (N = 10), diltiazem 10(-4) M (N = 6) and diltiazem 10(-4) M plus non-stimulation (N = 10).3. Isolated mt LV papillary muscles were studied in Krebs-Henseleit solution with a calcium concentration of 2.52 mM at 28-degrees-C while contracting isometrically at a stimulation rate of 0.2 Hz. Resting tension and active isometric tension were measured.4. Both diltiazem and quiescence significantly attenuated contracture tension during hypoxia (0.91 +/- 0.10 vs 2.26 +/- 0.49 g/mm2 for diltiazem vs control, and 0.55 +/- 0.18 vs 2.26 +/- 0.49 g/mm2 for quiescence vs control). Recovery of active tension was improved in the diltiazem groups during reoxygenation (4.16 +/- 0.42 vs 3.75 +/- 0.51, 3.53 +/- 0.15 vs 2.90 +/- 0.13, 5.84 +/- 0.33 vs 6.48 +/- 0.29 and 5.98 +/- 0.90 vs 7.67 +/- 0.68 g/mm2 for diltiazem, diltiazem non-stimulation, non-stimulation and control groups).5. The results suggest that the protective effect of diltiazem during hypoxia was due to the reduction in energy demand of the myocardium.
Keywords: ISOLATED PAPILLARY MUSCLE; DILTIAZEM; QUIESCENCE; HYPOXIA; HYPOXIC CONTRACTURE